Evaluating Hots and Lots in ‘English for Nusantara’: A Content Analysis af A Grade VII English Textbook - Fakhrillah, Agvy Rena; Suharyadi, Suharyadi (Universitas Pendidikan Mandalika, 2025)
In the 21st century, fostering critical thinking and problem-solving skills is essential for students. This study analyzes the manifestation of Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS) in the English textbook ‘English for Nusantara’ for Grade VII. HOTS involves higher-level cognitive processes such as analysis, evaluation, and creation, while LOTS focuses on recall and comprehension. Involving a qualitative research design with a content analysis approach, this study applied Revised Bloom’s Taxonomy, which categorize exercises into LOTS (remember, understand, and apply) and HOTS (analyze, evaluate, and create). A total of 116 exercises in the form of instructions and 67 exercises in the form of questions from listening, speaking, reading, and writing tasks were analyzed. To maintain consistency, inter-rater reliability was ensured, where the analysis was cross-verified through discussions with a validator. The findings show that LOTS dominates the exercises, with 81% of the exercises are in the form of instructions and 89% in the form of questions. This indicates a heavy emphasis on LOTS and suggests an opportunity for more HOTS integration. Based on these findings, the study recommends that teachers incorporate more HOTS-focused activities, and textbook authors should design future editions with a stronger emphasis on HOTS exercises to foster critical thinking skills. Such adjustments would better equip students to meet the demands of the 21st century.